Application of statistical process control (SPC) to the production system of an automotive manufacturing plant's welding shop in Malaysia - 405352 Halim Shah Hamzah; Sha'ri Mohd. Yusof; Fakulti Kejuruteraan Mekanikal (2005)
Thesis (Sarjana Kejuruteraan Mekanikal (Teknologi Pembuatan Termaju)) - Universiti Teknologi Malaysia, 2005